Stem cell strategies for cell replacement therapy in endocrine diseases - Chengjia Mi; Xie Cheng; JinYang Tang; Yang Gao; Jing Zhang; Yan Yang; Guixiang Tan; Chunbing Zheng; Haisong Liu (Cell Transplantation, 2026)
Conventional therapies for endocrine hormone deficiencies, including hormone replacement therapy and solid organ transplantation, are hampered by the lack of physiological regulation or donor shortage, respectively. Directed differentiation of human pluripotent stem cells has opened new avenues for cell replacement therapy; however, research on different endocrine glands has long been conducted in isolation, with limited cross-disciplinary exchange of technical expertise. This Review takes the clinically most advanced stem cell-derived pancreatic β cells as a methodological reference and establishes a three-tier translational challenge model—cell identity, in vivo survival, and functional delivery—to systematically compare the regenerative progress and specific hurdles of thyroid, parathyroid, pituitary, and adrenal cells. We highlight transferable strategies emerging from these lineage-specific studies, including temporal developmental signaling modulation, modular lineage assembly, prevascularization engineering, and hierarchical immunocompatibility design. Through this cross-lineage comparative framework, this Review aims to break the isolated research paradigm and provide a methodological foundation for endocrine regenerative medicine to evolve from isolated efforts toward synergistic advancement.